PEMANFAATAN MEDIA SOSIAL PADA BAGUS TAILOR - Meta Utari; Boyke Nugrahanto (JURNAL AKADEMIK EKONOMI DAN MANAJEMEN, 2026)
The digital era has impacted various fields, including marketing, which requires business actors to utilize social media as a promotional tool. In practice, Bagus Tailor has not utilized social media optimally, so marketing activities are still dominated by traditional methods and have an impact on less than optimal sales. This study aims to analyze the use of social media, obstacles in using social media, and strategies for utilizing social media at Bagus Tailor. This study uses a qualitative approach with a case study method. Data collection techniques were carried out through in-depth interviews, observation, and documentation with informants consisting of owners, employees, and customers. Data analysis was carried out using NVivo software through a process of coding, categorization, and theme extraction. The results of the study indicate that social media, especially Instagram and WhatsApp, are used as a means of promotion, delivering service information, and direct communication with customers, thereby increasing market reach, purchasing power, and customer loyalty, which has an impact on increasing sales. However, there are obstacles in the use of social media such as limited time, digital skills, human resources, and consistency in content management. To overcome these obstacles, a social media utilization strategy is needed through consistent content upload scheduling, increasing digital competency, optimizing social media features, and strengthening interactions with customers so that digital marketing can run more effectively and sustainably.